Improved control strategies for a DFIG-based wind-power generation system with SGSC under unbalanced and distorted grid voltage conditions. (May 2016) - Yao, Jun; Yu, Mengting; Hu, Weihao; Chen, Zhe; Zhou, Te
Highlights: Performance of DFIG with SGSC under unbalanced and distorted voltage are enhanced. Three sets of selectable control targets for PGSC are identified. Allocations for the PGSC's current references is studied by considering its limit. PI-DFR controller are designed to regulate corresponding components simultaneously. Realize generator under normal operation and suppress pulsations of output powers. Abstract: This paper investigates an improved control strategy for a doubly-fed induction generator (DFIG) based wind-power generation system with series grid-side converter (SGSC) under network unbalance and harmonic grid voltage distortion conditions. The integrated mathematical modeling of the DFIG system with SGSC is established by taking both the negative-sequence and harmonic components of the grid voltages into consideration with multiple synchronous rotating reference frames. Under network unbalance and harmonic distortion situations, stator voltage can be kept symmetrical and sinusoidal by the control of SGSC, which indicates that the rotor-side converter (RSC) can be still controlled with the traditional vector control strategy without modifications. Meanwhile, for the parallel grid-side converter (PGSC), three sets of selectable control targets are identified and their corresponding current references are calculated. In addition, the allocation principles for the PGSC's current references are proposed by taking into account the PGSC's current rating limit. The impact of PGSC's current limit on the proposed control strategies have been investigated in detail. Furthermore, a PI regulator with a dual-frequency resonant (PI-DFR) controller in the positive synchronous reference frame for PGSC and SGSC are designed to achieve the rapid and precise regulation of the corresponding components simultaneously. Simulation studies on a DFIG system with SGSC under network unbalance and harmonic distorted voltage situation validate the proposed control strategies and allocation principles for PGSC's current reference.